Peran penyuluhan pajak terhadap inefisiensi pemungutan pajak di Indonesia - Nova Sari Dewi; Benedictus Raksaka Mahi (Jurnal Ekonomi Modernisasi, 2022)
One of the strategies of collecting taxes in Indonesian territory is through tax education as an effort to increase taxpayer awareness. PERMAN-RB No. 49 and PERMAN-RB No. 50 of 2020 show that the function of tax education is essential in tax collection. This study analyzed the effect of tax education on the inefficiency of tax collection in Indonesia. The method used in this study is Stochastic Frontier Analysis with a one-step estimation approach from 319 Primary Tax Service Offices in 2017-2020. The output variable used in this study is the realization of tax revenue, while the input variable used is capital per labor. This study also uses control variables which are: population density, education, the number of informal workers, the number of MSME taxpayers registered in the primary tax service office, and the number of non-SME taxpayers registered in the primary tax service office. The results show that the efficiency level of the primary tax service office in Indonesia with an average technical efficiency in 2017-2020 is 89.45% hence 10.45% identified, which can be optimized to get the most efficient operational level. Tax education has a negative effect on the inefficiency of the Primary Tax Service Office.